(untitled) (Research, Society and Development, 2021)
The Apiculture project in early childhood education: Interacting with bees to know, preserve and consume was implemented in 2019 on the premises of the Tancredo de Almeida Neves Campus (CTAN) at the Federal University of São João del-Rei (UFSJ). The promotion of knowledge about the diversity of bee species (melipona - stingless bees or honeybee - stinging bee), beekeeping activities, their products and the interaction of bees with the environment, aims to arouse children’s interest in the preservation of colonies, the valorization of bee products, and greater acceptance of the implementation of honey in school lunches. At the end of the first year of the project’s realization, the first reflections of the work carried out were noted: two schools participating in the project requested from the city government the demand for 3,000 honey sachets for public calls through the National School Feeding Program (PNAE), for the acquisition of foodstuffs from Family Farming, for school feeding.